SENSORY EVALUATION OF LEMONGRASS BEVERAGE MIXED WITH AGARWOOD INFUSION USING 9-POINT HEDONIC SCALE - Aini, Husnul; Kurnia, Nova; Wangiyana, I Gde Adi Suryawan (Universitas Pendidikan Mandalika, 2024)
Lemongrass and agarwood are potential forest herbal tea products which need to be further explored based on research and development schemes. The purpose of this research is to conduct a sensory evaluation using a 9-point hedonic scale and different statistical approaches on mixed lemongrass beverages and agarwood infusion. Four treatments are used in this research including: L1 = Lemongrass concentration 0.1% w/v, L2 = Lemongrass concentration 0.2% w/v, L3 = Lemongrass concentration 0.3 % w/v, L4 = Lemongrass concentration 0.4% w/v. This research used 4 different statistical approaches including Kruskal-Wallis, Freidman Test, ANOVA-CRD, and ANOVA-RBCD. Sensory evaluation was conducted using a 9-point hedonic scale using 30 trained respondents on 4 parameters including appearance, aroma, taste and bitterness. The results show that all statistical approaches give sensitive analysis for P-value measurement except for the Freidman Test. Appearance is the only parameter with a significant p-value in all statistical approaches. Different treatments show different maximum hedonic score values on different parameters, and they are significantly different based on DMRT results. However, based on the area of the spider web chart, L2 has the largest impact on hedonic score value compared to other treatments. It could be concluded that Treatment L2 (lemongrass concentration of 0.2% w/v) has the highest hedonic evaluation score which shows that this is the effective concentration to produce beverage products with good acceptability.